In situ surface analysis of novel marine foul-release coatings - Kenny, Stephen (2017)
Exposure of artificial surfaces such as ship hulls to a marine environment leads to the attachment of assorted biomolecules, single celled organisms and marine invertebrates such as barnacles or mussels. Together, they form a structure known as a biofilm. These films lead to higher fuel consumption and add considerable expense to the operation of ships used by industrial and naval organisations. The work presented in this thesis describes the surface analysis of a novel poly(dimethylsiloxane) (PDMS) based foul-release coating. The coating also contains poly(ethylene glycol) groups (PEG). The differing chemical properties between these two domains led to an observed surface modification effect in water, whereby contact angle measurements decreased from ~110o to ~65 o over a period of five minutes. This effect was rapidly reversible on drying. Time of Flight-Secondary Ion Mass Spectrometry cryogenic depth profiling experiments confirmed this change in surface chemistry where the frozen surface of the coating was shown to have a higher intensity of ions associated with PEG groups at the surface compared to that in the bulk. Water immersion also led to a swelling of the surface seen by a change in the surface topography by Atomic Force Microscopy investigations.